Perlindungan Hukum Terhadap Konsumen Apartemen Paragon Square Akibat Wanprestasi - Kusumawati, Marissa; Zamroni, M.; Romadhon, Ahmad Heru (Universitas Muhammadiyah Ponorogo, 2025)
Apartments are included in the Commercial Apartment category as regulated in Article 1 number 10 of Law Number 20 of 2011 concerning Apartments (UURS), which are organized for commercial purposes to gain profit. In practice, developers as business actors often conduct promotions by offering various facilities and advantages of apartment units to consumers. However, it is not uncommon for the promised facilities to be not fulfilled, or the units are not handed over on time as stated in the Sales and Purchase Agreement (PPJB), resulting in default. This study aims to analyze the forms of default committed by developers in the delivery of apartment units and examine the form of legal protection for consumers who are harmed. The research method used is normative juridical with a statutory approach and literature study. The results of the study indicate that defaults committed by developers cause material losses and legal uncertainty for consumers, and place consumers in a weaker legal position in sales and purchase transactions. Legal protection for consumers should be sought through fair and balanced agreements, but in reality the PPJB has not provided adequate legal certainty. In the event of a default, consumers have the right to demand compensation as regulated in Articles 1238, 1243, and 1249 of the Civil Code, and can seek dispute resolution as regulated in Article 105 of the UURS through litigation in court.